Kajian Teologis Hubungan Suami Istri Yang Kokoh Berdasarkan Efesus 5:22-33 - Perangin Angin, Yakub Hendrawan; Yeniretnowati, Tri Astuti (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
In every marriage and family as an institution established by Allah, Allah has established rules, roles, and responsibilities for each person in the household. The goal of a Christian marriage or family will not be achieved if the underlying relationship between husband and wife is not based on the truth that God has ordained. The path that humans take, including believers in building harmonious relationships in their marriage, is often not smooth, sometimes even unsuccessful and meets this destruction because it does not apply the pattern that has been declared by God as written in Ephesians 5; 22-33 as a pattern specifically and the standards of Christian husband and wife relationships that run according to God's provisions.AbstrakDalam setiap pernikahan dan keluarga sebagai sebuah lembaga yang ditetapkan Allah, maka Allah sudah menetapkan aturan, peran, tanggung jawab untuk setiap pribadi dalam rumah tangga itu. Tujuan pernikahan atau keluarga Kristen tidak akan tercapai kalau hubungan yang mendasari suami dan istri tidak berdasarkan kebenaran yang Allah sudah tetapkan. Jalan yang manusia tempuh termasuk orang percaya dalam membangun relasi yang harmonis di dalam pernikahnnya sering kali tidak mulus bahkan tidak jarang yang tidak berhasil dan menemui kehancuran hal ini karena tidak menerapkan pola yang sudah dinyatakan oleh Allah sebagaimana tertulis dalam Efesus 5;22-33 sebagai pola khusus dan standar hubungan suami istri Kristen yang berjalan sesuai ketetapan Allah.